Powerful presentations : selling your story on stage or in the boardroom - Haunts, Stephen (Apress, 2022)
Unlock your potential and understand how you can have an audience hanging on to your every word. Entrepreneurs and business professionals often have to pitch their products and projects to an audience - whether at a conference stage, meetup group, to VC firms or even at the office to their peers and leaders. Through this book, you will learn how to plan, rehearse, and deliver the perfect presentation for your needs. You'll review different presentation styles, how to craft and structure a talk and how to make it engaging for the audience. If you've ever wondered how you can be chosen to speak at a conference, this book will show you how and go in depth on how to craft a winning talk synopsis and proposal to stand out over the competition. You'll also examine many other details that go into giving a presentation such as face and hand gesturing, pre-performance rituals like visualization techniques, time management , addressing technical difficulties, preparing for question-and-answer sessions, gathering feedback, the differences between in person events and online talks/webinars and how to mold your presentation to the medium. Powerful Presentations will show you how to perfect your public speaking and presentation skills.
Includes index.
Keywords: Business presentations.; Public speaking.; elektronické knihy; electronic books